Unequal bonds: social capital, equity and displacement outcomes in Nigeria - Onuoha, John Mba; Ihinegbu, Christopher; Ihinegbu, Rosemary Daniella; Owube, Dominic T. (Frontiers in Human Dynamics, 2026)
With the growing intensity of climate change, alongside increasing conflicts, terrorism, and development-induced evictions, displacement has become more prevalent—particularly among vulnerable communities. Existing studies on displacement and social capital have examined how displacement affects social capital and how social cohesion can enhance resilience. However, few have explored how the impacts on social capital vary by displacement type and across equity dimensions. This brief report, part of a larger study investigating the drivers and impacts of displacement, examines the effects of social capital and equity dimensions on four types of displacement: environmental, political, economically driven, and conflict-driven. Using a multi-stage sampling method, 400 questionnaires were administered to displaced individuals across the six area councils of Abuja, Nigeria, proportionate to population size. Preliminary findings reveal that social capital has the most significant impact on economic-driven displacements and that social capital is negatively associated with environmental displacement. Across displacement types, men are more likely to be displaced, especially economic displacements. Homeownership, age, and education level show inconsistent associations with displacement type. The preliminary findings highlight the crucial role of social capital and equity-related socioeconomic variables in shaping exposure to different types of displacement. This preliminary report offers recommendations to inform the broader ongoing study and underscores the importance of resilience-building for both environmental- and non-environmental-related displacements.